THE ROLE OF GEOGRAPHIC TERMS DEFINITION HIGH RELIEF FORMS IN THE FORMATION OF ORONYMS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In the article, the importance of height relief forms in the formation of mountains is analyzed on the example of mountains of Uzbekistan. The terms representing the most important elevational relief forms involved in the formation of oronyms have been determined and the toponyms involved in them have been studied geomorphological.